2015
DOI: 10.1002/anie.201502890
|View full text |Cite
|
Sign up to set email alerts
|

The Expanded Genetic Alphabet

Abstract: All biological information, since the last common ancestor of all life on earth, has been encoded by a genetic alphabet consisting of only four nucleotides that form two base pairs. Long standing efforts to develop two synthetic nucleotides that form a third, unnatural base pair (UBP) have recently yielded three promising candidates, one based on alternate hydrogen bonding, and two based on hydrophobic and packing forces. All three UBPs are replicated and transcribed with remarkable efficiency and fidelity, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
174
0
9

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 184 publications
(186 citation statements)
references
References 209 publications
3
174
0
9
Order By: Relevance
“…6 In contrast to the natural nucleotides, the pairing of these unnatural nucleotides relies on hydrophobic and packing forces as opposed to complementary hydrogen bonding. While the development of this UBP required years of optimization, 8 the completely unnatural mode of pairing between the nucleobases of the UBP is expected to bestow them with an inherent orthogonality, with respect to their mispairing with the natural nucleotides and to their recognition by proteins that recognize the natural triphosphates (including the many proteins that interact with the triphosphates outside of information storage and retrieval). In 2014, with the aid of a nucleoside triphosphate transporter to import the unnatural triphosphates, we showed that a precursor of the d NaM -d TPT3 UBP may be retained within the DNA of growing and dividing E. coli , 12 and more recently, with the use of SpCas9 directed to eliminate sequences that have lost the UBP, we showed that d NaM -d TPT3 is retained in the DNA of the SSO with fidelity approaching that of a natural base pair.…”
mentioning
confidence: 99%
“…6 In contrast to the natural nucleotides, the pairing of these unnatural nucleotides relies on hydrophobic and packing forces as opposed to complementary hydrogen bonding. While the development of this UBP required years of optimization, 8 the completely unnatural mode of pairing between the nucleobases of the UBP is expected to bestow them with an inherent orthogonality, with respect to their mispairing with the natural nucleotides and to their recognition by proteins that recognize the natural triphosphates (including the many proteins that interact with the triphosphates outside of information storage and retrieval). In 2014, with the aid of a nucleoside triphosphate transporter to import the unnatural triphosphates, we showed that a precursor of the d NaM -d TPT3 UBP may be retained within the DNA of growing and dividing E. coli , 12 and more recently, with the use of SpCas9 directed to eliminate sequences that have lost the UBP, we showed that d NaM -d TPT3 is retained in the DNA of the SSO with fidelity approaching that of a natural base pair.…”
mentioning
confidence: 99%
“…This intercalation appears to be driven by favorable stacking of the large aromatic surfaces of each d PICS nucleobase, and has been observed with other nucleotides bearing nucleobase analogs with extended aromatic surface area. 18 We hypothesized that the same mode of pairing occurs at the primer terminus, which we envisioned would account for the efficient rates of UBP synthesis, but also the inefficient rates of continued extension, as de-intercalation would be required to appropriately position the primer terminus.…”
Section: A Structural Interludementioning
confidence: 99%
“…While the idea to create a third base pair to enhance the genetic alphabet dates back to 1962 [41], it took numerous iterations of additional base pairs to attain some that were able to be incorporated into normal DNA strands and amplifiable with satisfactory fidelity without the risk of mispairing with the natural nucleobases [42]. By now, three different groups published well-characterized novel base pairs with properties that allow their use in aptamer selections: Romesberg's group is working with dNaMd5SICS (dNaM: 1,4-Anhydro-2-deoxy-1-C-(3-methoxy-2-naphthalenyl)-(1R)-D-erythro-pentitol, d5SICS: 2-((2R,4R,5R)-tetrahydro-4-hydroxy-5-(hydroxymethyl) furan-2-yl)-6-methylisoquinoline-1(2H)-thione), Hirao and co-workers have published dDs-dPx (Ds: 7-(2-thienyl)imidazo [4,5-b]pyridine, Px: 2-nitro-4-propynylpyrrole), and Benner's laboratory is utilizing the dZ-dP (dZ: 6-amino-5-nitro-3- (Figure 4).…”
Section: Aptamers With An Extended Genetic Alphabetmentioning
confidence: 99%
“…(c) The dDs-dPx base pair from Hirao's group, of which dDs has been used for aptamer selections [43 ]. (d) The d5SICS-dNaM base pair from Romesberg's group [42].…”
Section: Aptamers With An Extended Genetic Alphabetmentioning
confidence: 99%